The C-MAC videolaryngoscope for prehospital emergency intubation: a prospective, multicentre, observational study. Issue 8 (21st March 2011) - Cavus, Erol; Callies, Andreas; Doerges, Volker; Heller, Gilbert; Merz, Sabine; Rösch, Peter; Steinfath, Markus; Helm, Matthias
Abstract : Background: In this preliminary prospective observational study at four physician-led air rescue centres, the efficacy of the C-MAC (Karl Storz, Tuttlingen, Germany), a new portable videolaryngoscope, was evaluated during prehospital emergency endotracheal intubations. Methods: 80 consecutive patients requiring prehospital emergency intubation, treated by a physician introduced in the use of the C-MAC were enrolled in this study. Results: Indication for prehospital intubation was trauma in 45 cases (including maxillo-facial trauma in 10 cases), cardiopulmonary resuscitation in 14 cases, and unconsciousness of neurological aetiology and cardiogenic dyspnoea in 21 cases. Forty-nine patients were intubated with a C-MAC blade size 3, and 31 with a C-MAC blade size 4. Median time to successful intubation was 20 (min−max: 5−300) seconds; 63 patients were intubated on the first attempt, 13 on the second and four after more than two attempts. A Cormack-Lehane class 1 view of the glottis was seen in 46 patients, class 2a view in 21, class 2b in eight, class 3 in three and class 4 in two. Six patients could not be intubated with the videolaryngoscopic view, but were successfully intubated at the same attempt using the C-MAC with the direct laryngoscopic view. Conclusion: The C-MAC videolaryngoscope was suitable for prehospital emergency endotracheal intubations with complicated airway conditions, such as maxillo-facial trauma. The option to perform direct laryngoscopy and videolaryngoscopy with the same device appears to be exceptionally important in the prehospital setting.